Peningkatan Kapasitas Guru Dalam Pengembangan Media Pembelajaran Unsynchronous Learning - Yuana, Kumara Ari; Rahayu, Dwi; Mulyatun, Sri; Widowati, Anik Sri (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
The pandemic period led to changes in learning methods. One of the learning methods that are effective now is the direct learning method (Synchronous Learning) and the indirect method (Unsynchronous Learning). Perambanan Social Vocational High School 1 has developed the learning system but has yet to maximize learning media development. Therefore, there is a need for training and workshops to increase teachers' knowledge to solve the problems encountered related to making learning media. The service is carried out through several stages: identifying activities, planning and implementing activities, follow-up and evaluation, and preparing reports. The results of the service show that participants not only have the ability to develop learning media but also have a deeper understanding of the benefits of technology in learning. The teachers involved are expected to strengthen their abilities in developing creative and relevant learning content according to the needs of students. This effort can potentially improve the quality of learning, expand accessibility for students to learn flexibly, and present a more interactive and exciting learning experience.